Establishing in vitro models of neuroinflammation to investigate neuroimmune responses in neurocysticercosis - Awala, Amalia Naita (Department of Human Biology, 2024)
Neurocysticercosis (NCC), a parasitic infection of the central nervous system (CNS) caused by the larvae of the cestode Taenia solium, is the leading cause of adult-acquired epilepsy in the world. A surprising clinical manifestation of NCC is that viable larvae can exist in the brain for extended periods with no symptomatology, but when they die, clinical symptoms develop. Clinical evidence suggests that the hallmark of symptomatic NCC is neuroinflammation; however, the neuroinflammatory mechanisms underlying this disease remain grossly understudied, and how innate immune cells respond to this infection is still debated. One of the reasons for this is that there is a lack of reliable experimental models of inflammation at the level of the brain that allow for cell-type specific tracking of inflammation in innate immune cells. Thus, this thesis's first aim was to establish the rodent-derived organotypic brain slice culture (OBSC) system as an in vitro model for investigating neuroinflammatory signalling and activation of microglia and astrocytes in the brain. To validate this model of neuroinflammation, OBSCs from neonatal mice were treated with the pro-inflammatory stimulant lipopolysaccharide (LPS) for 24 hours and compared to untreated control slices. Inflammatory activation of microglia and astrocytes was measured by tracking the activation of the inflammatory transcription factor nuclear factor for interleukin 6 (NF-IL6), a robust biomarker for tracking neuroinflammation in glial cells. Inflammation was confirmed by measuring the concentrations of pro-inflammatory cytokines IL-6 and TNF-α released by OBSCs in the culture medium. Lastly, we used single-nucleus RNA sequencing to investigate these inflammatory changes at a transcriptomic level. My results show that LPS significantly increased NF-IL6 activation in microglia and astrocytes and increased the release of both IL6 and TNF-α. At the transcriptomic level, I observed an upregulation of major inflammatory genes such as CCL5 and Timp1 in both microglia and astrocytes in response to LPS treatment, further confirming inflammation. Having demonstrated that OBSCs present a robust platform for investigating neuroinflammatory mechanisms in brain infections, the second aim of this thesis sought to use this established model to investigate how viable Taenia larvae modulate neuroinflammation in NCC. The potential immunomodulatory effects of the Taenia larvae on glial activation and inflammation was assessed by concurrently treating OBSCs with both LPS and Taenia larvae homogenate. I found that the co-application of LPS and Taenia larvae homogenate suppressed the LPS-induced microglial and astrocytic activation, proinflammatory cytokine release, and prevented the upregulation of key inflammatory genes. Together, this observed anti-inflammatory effect could explain how Taenia larvae can exist in the human brain without eliciting symptomatology from the host. This thesis's final aim was to set up a comparable translational in vitro human model of neuroinflammation using human II acute and organotypic brain slice cultures (hOBSCs). Using the inflammatory transcription factor NF-IL6 as a marker for glial activation, I found that at baseline, hOBSCs displayed higher levels of microglial and astrocytic activation than human acute slices. Additionally, untreated control and LPS-treated hOBSCs both displayed high levels of NF-IL6 activation. However, cytokine data revealed low concentrations of pro-inflammatory cytokines IL-6 and TNF-α in culture medium in untreated control hOBSCs that increased when slices were exposed to LPS, highlighting an inflammatory reaction. Taken together, these findings provide novel insights into understanding the neuroinflammatory mechanisms underlying NCC and highlight the utility of organotypic brain slice cultures in studying neuroimmune responses in diseases of an inflammatory nature such as NCC.